Innovations in the Tanning Industry Oriented at Improving the Environmental Profile of Leather - Gabriela ZIELINSKA (Communications of International Proceedings, 2021)
The leather industry is one of the most resource-consuming sectors of the economy, and therefore requires transformation aimed at managing water, energy, raw materials, and waste in accordance with the principles of sustainable development. The article presents new solutions in the fields of the substitution of chromium, which is a threat to the environment, and effective methods of wastewater treatment for recovery of valuable components and their reuse in the technological processes. New methods of tannery waste management, enabling the recycling of materials and energy, are presented. The article also presents the effects of changes made in the leather industry in the last few years, as well as legal regulations which force evolution of the leather production processes.
Keywords: Tanning industry; Environmental profile of leather; Innovations